Pelatihan Pembuatan Business Model Canvas Bagi Usaha Kecil Menengah Sidayu Gresik - Yanuar Pandu Negoro; Said Salim Dahda (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
The potential and role of MSMEs, which has a large portion of employment and its influence on gross domestic product, makes MSMEs the prima donna of the Indonesian economy. The growth rate that has not met the target and the development of MSME businesses still does not show a positive value in East Java in particular is a concern for improvement. Business processes are the most common problem faced by MSME players. The limitations possessed by MSMEs as well as the abstract form and the many influencing factors make business process identification difficult for MSMEs. By introducing Business Model Canvas (BMC), which can reduce the complexity of creating business processes, MSMEs can identify business processes. In this service, an explanation was given to the MSME association in Sidayu Gresik sub-district regarding the importance of business processes for a business. And in the end, MSMEs are invited to learn to identify their business processes with BMC.